Strategi Guru Mengajak Anak Berkebutuhan Khusus Untuk Bersemangat Ke Sekolah - Disa Ananda; Revydo Prayogi; Sri Wahyuliawati; Ulam Arta Gabriela; Opi Andriani (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
Teachers have their own strategies so there is no common perception regarding teachers' strategies for getting children with special needs to be enthusiastic about going to school. This research aims to explore teachers' strategies for encouraging children with special needs to be enthusiastic about going to school. The research subject was a teacher who taught 1 child with special needs. The sampling technique is by using purposive sampling technique. Data was obtained through an open-ended questionnaire (open questions). The method used is qualitative with analysis using coding techniques. The research design used uses an indigenous psychology approach, part of the scientific approach tradition, where the important aspect in this approach is the effort to find appropriate strategies to uncover phenomena in an investigation. The research results showed that there were problems encountered by teachers, such as a lack of strategies in getting children with special needs to be enthusiastic about going to school.